GLOBALISM OF EVOLUTIONISM - Hałaczek, Bernard (Studia Philosophiae Christianae, 2020)
The phenomenon of globalization, which is well known in the economy, can nowadays be observed also in the area of science. It is based on the fact that more and more scientific disciplines are applying the same explanatory principle, namely the theory of evolution. Therefore, every development, including that of man, according to the pattern of genetic reproduction, takes place on the basis of natural selection. With psychological properties, mental abilities and social behaviours, which are eloquently referred to as “memes”, it is as with genes: only those that are better, stronger, more capable of surviving will survive after accidental changes and only they will be passed on. In short, reproduction regulates and controls human behaviour. Such a way of thinking and explanation can be found today in many publications on sociobiology and evolutionary psychology. Even if they present many new details, they pay tribute to the old human desire to explain everything in a simple way, according to the same scheme. The same expectation towards science was expressed by E. Haeckel in the 19th century and J. Monod in the 20th century. However, when these two biologists explained man as a whole based on the theory of evolution, they admitted that they referred to philosophy, to which contemporary representatives of sociobiology and evolutionary psychology cannot or do not want to confess.